Main drivers of (poly)phenol effects on human health - Iglesias-Aguirre, Carlos E. (2021)
Funding Information: This research was supported by the Project PID2019-103914RB-I00 from the Ministry of Science and Innovation (MICINN, Spain) and by Fundación Séneca de la Región de Murcia (Spain), grant number 20880/PI/18. J.A.G.-B. was supported by a Standard European Marie Curie Fellowship from the European Commission. This project has received funding from the European Union’s Horizon 2020 research and innovation program under the Marie Sklodowska-Curie grant agreement no. 838991. A.C.M. and C.E.I.-A. are the holders of predoctoral grants from MINECO (grant number BES-2016-078098) and MICINN (grant number FPU18/03961) (Spain), respectively. Publisher Copyright: © 2021 The Royal Society of Chemistry.